The Sociocultural Context of Psychosocial Interventions - Tim Lomas (Frontiers Research Topics, 2018)
Across diverse academic fields, scholars and practitioners are engaged in developing interventions to promote outcomes like health and quality of life. Indeed, such is the apparent efficacy of such interventions, that there are many policy-led initiatives to implement these at national and international scales. However, few scholars or practitioners have thought in any systematic and critical way about the importance of contextualizing these interventions, i.e., considering how the impact of such interventions may be affected and mediated by specific sociocultural factors (from gender, to ethnicity and socio-economics). The aim of the Research Topic "The Sociocultural Context of Psychosocial Interventions" was to address this lacuna. As such, we tried to help bringing a more 'contextual' mindset to the implementation of health and wellbeing interventions. This may help to shift the way such interventions are designed and implemented, both at a granular local level (i.e., influencing individual practitioners) and at a large-scale macro level (e.g., influencing policy makers). Themes within this Research Topic have concerned both macro-sociocultural as well as meso-and micro-layers, and the peculiarities of implementing real world research based on these levels. There has been room for physical and mental health, for family relationships, for educational contexts and even for the effects of crime. Some works have included interesting methodological discussions on the integration of different ecological layers or the modal distribution of our interests. For us it has been very important to work giving a greater diffusion to these issues since, considering psychosocial interventions in the context in which they occur, goes beyond an epistemological or methodological discussion. Rather, these considerations seriously affect the ability of practitioners to really reach the people who need their interventions, listening to their needs and respecting their preferences. For the editors of this book, then, the contextualization of interventions means considering the people who receive them as full citizens immersed in complex societies where factors such as social justice and health or well-being do not float apart in space but affect each other dialectically. We therefore think that the duty of both academics and practitioners is not to forget that it is as important to evaluate the direct effect of our interventions as the influence we have in the society as a whole when we carry them out. We hope you enjoy reading these works and that their dissemination stimulates new lines of research committed to both good practice and social transformation.